Efficacy assessment of liposome crosslinked hyaluronic acid and standard hyaluronic acid eye drops for dry eye disease management: a comparative study employing the ocular surface analyzer and subjective questionnaires - Sánchez-González, José-María; De-Hita-Cantalejo, Concepción; González-Rodríguez, María Luisa; Fernández-Trueba-Fagúndez, Ana; Ballesteros-Sánchez, Antonio; Martinez-Perez, Clara; Caro-Díaz, Romina; Guzman, Carla Montiel; González-Oyarce, María Fernanda; Sánchez-González, María Carmen (Frontiers in Medicine, 2024)
Dry eye disease (DED) is a prevalent condition causing ocular discomfort and visual disturbances, often managed with artificial tears. This study aimed to assess and compare the efficacy of eye drops containing Crosslinked Hyaluronic Acid (CHA) with liposomes and crocin and standard Hyaluronic Acid (HA) for DED management. A single-blind, longitudinal study was conducted on 24 participants (48 eyes), randomized to receive one of the two treatments. Ocular health measures, including the ocular surface disease index (OSDI) and the standard patient evaluation of eye dryness (SPEED) scores, were assessed at baseline and six weeks post-treatment using the Ocular Surface Analyzer. CHA achieved a lipid layer thickness increase of 1.29 ± 1.08 Guillon pattern degree (p < 0.01), FNIBUT increase 0.64 ± 0.77 seconds (p < 0.01), MNIBUT increase 1.28 ± 4.74 seconds (p = 0.19), OSDI decrease 11.72 ±6.73 score points (p < 0.01) and SPEED decrease 1.16 ± 5.05 score points (p = 0.27). Significant reductions in the OSDI and SPEED scores post-treatment were observed with both treatments, indicating their effectiveness. CHA with liposomes exhibits superior efficacy compared to standard HA eye drops in the management of DED. These findings highlight the potential for personalized treatment strategies incorporating CHA, indicating a more effective approach to DED management. However, further research is required to validate these results and investigate the long-term effects, which may pave the way for a data-driven and optimized approach to managing DED.